2019
DOI: 10.4103/ijdvl.ijdvl_482_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of disease severity in drug reaction with eosinophilia and systemic symptoms

Abstract: Studies on the predictors of severity in drug reaction with eosinophilia and systemic symptoms in different population groups may enable us to identify the warning signs and help to formulate the standard therapeutic guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
15
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 0 publications
6
15
5
Order By: Relevance
“…Though, two of the patients denied any history of prior exposure, it is possible that same or a related drug may have been taken by the patient earlier. This rapid onset of symptoms on second exposure has been reported previously 10,12‐14 . Commonly reported culprit drugs were sulpha group (five with dapsone and two with Sulphasalazine) followed by aromatic AED (Phenytoin: five, Oxcarbazine:one).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Though, two of the patients denied any history of prior exposure, it is possible that same or a related drug may have been taken by the patient earlier. This rapid onset of symptoms on second exposure has been reported previously 10,12‐14 . Commonly reported culprit drugs were sulpha group (five with dapsone and two with Sulphasalazine) followed by aromatic AED (Phenytoin: five, Oxcarbazine:one).…”
Section: Discussionsupporting
confidence: 80%
“…However, this correlation did not reach statistical significance possibly due to a small sample size. Liver was the commonest internal organ affected in 14 (70%) patients with comparable frequency to study by Sasidharanpillai et al 10 But its involvement in DRESS has been reported more frequently in European and eastern countries 4,8,12 . The difference could be due to racial distribution and regional drug profile 19 .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…2 A larger cross-sectional study that evaluated all patients with DRESS who were treated in our department since 2011 confirmed our earlier findings; in addition, we noted that the interval of less than 2 weeks between the beginning of drug intake and the appearance of symptoms was not unique to DRESS precipitated by antibiotics. 2,3 (We had included both probable and definite cases of DRESS, as per RegiSCAR (Registry of Severe Cutaneous Adverse Reaction) DRESS validation scoring system. )…”
mentioning
confidence: 99%